Methylation risk scores for childhood aeroallergen sensitization: Results from the LISA birth cohort. Issue 9 (2nd May 2022) - Kilanowski, Anna; Chen, Junyu; Everson, Todd; Thiering, Elisabeth; Wilson, Rory; Gladish, Nicole; Waldenberger, Melanie; Zhang, Hongmei; Celedón, Juan C.; Burchard, Esteban G.; Peters, Annette; Standl, Marie; et al.
Abstract: Background: Epigenomic (e.g., DNA methylation [DNAm]) changes have been hypothesized as intermediate step linking environmental exposures with allergic disease. Associations between individual DNAm at CpGs and allergic diseases have been reported, but their joint predictive capability is unknown. Methods: Data were obtained from 240 children of the German LISA cohort. DNAm was measured in blood clots at 6 ( N  = 234) and 10 years ( N  = 227) using the Illumina EPIC chip. Presence of aeroallergen sensitization was measured in blood at 6, 10, and 15 years. We calculated six methylation risk scores (MRS) for allergy‐related phenotypes, like total and specific IgE, asthma, or any allergies, based on available publications and assessed their performances both cross‐sectionally (biomarker) and prospectively (predictor of the disease). Dose–response associations between aeroallergen sensitization and MRS were evaluated. Results: All six allergy‐related MRS were highly correlated ( r  > .86), and seven CpGs were included in more than one MRS. Cross‐sectionally, we observed an 81% increased risk for aeroallergen sensitization at 6 years with an increased MRS by one standard deviation (best‐performing MRS, 95% confidence interval = [43%; 227%]). Significant associations were also seen cross‐sectionally at 10 years and prospectively, though the effect of the latter was attenuated when restricted to participants not sensitized at baseline. A clear dose–response relationship with levels of aeroallergen sensitization could be established cross‐sectionally, but not prospectively. Conclusion: We found good classification and prediction capabilities of calculated allergy‐related MRS cross‐sectionally, underlining the relevance of altered gene‐regulation in allergic diseases and providing insights into potential DNAm biomarkers of aeroallergen sensitization. Abstract : We calculated six MRS for allergy‐related phenotypes and present their association with childhood aeroallergen sensitization. All six allergy‐related MRS were highly correlated and seven CpGs were overlapping between the MRS, all located in genes associated with allergic diseases. A clear dose–response relationship with levels of aeroallergen sensitization could be established cross‐sectionally, but not prospectively.Abbreviations: ACOT7, acyl‐CoA thioesterase 7; CpG, cytosine–guanosine dinucleotide; LISA, influence of lifestyle factors on development of immune system and allergies in east and west Germany study; MFHAS1, multifunctional ROCO family signaling regulator; MRS, methylation risk score; SEC16B, SEC16 homolog B, endoplasmic reticulum export factor; ZFPM1, zinc finger protein, FOG, family member 1